Conceptual approach and fundamental aspects for a low-carbon energy matrix - Barros, Eduardo Lopes de; Misságia, Pablo Cardoso; Oliveira, Odilon Junio Gonçalves de; Feroni, Wilson José; Missagia, Monique Silvares; Tesolini, Victor de Barcellos Tesolini; Feroni, Rita de Cassia; Xavier, Thiago Padovani (Latin American Journal of Energy Research, 2025)
The energy transition toward a low-carbon matrix is essential for mitigating climate change and meeting international targets such as those outlined in the Paris Agreement. This study analyzes the concepts and challenges of this transition, focusing on low-carbon technologies, carbon markets, and energy policies. A systematic literature review and a comparative analysis of successful cases were conducted, considering emission measurement methodologies and decarbonization strategies. The results indicate that energy diversification, combined with regulatory incentives and technological innovations, is fundamental to accelerating the transition. It is concluded that effective policies, sustainable financing, and integrated technological development are essential to achieving a resilient and low-carbon energy system
Keywords: Decarbonization, Energy Policies, Circular Economy, Energy Efficiency, Carbon Credit Market, Energy Planning.